2011
DOI: 10.1007/s11629-011-2051-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the two filling functions for the recovery of forest information in mountainous shadows on Landsat ETM + Image

Abstract: In general, topographic shadow may reduce performance of forest mapping over mountainous regions in remotely sensed images. In this paper, information in shadow was synthesized by using two filling techniques, namely, roifill and imfill, in order to improve the accuracy of forest mapping over mountainous regions. These two methods were applied to Landsat Enhanced Thematic Mapper (ETM +) multispectral image from Dong Yang County, Zhejiang Province, China. The performance of these methods was compared with two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Shadow detection using a histogram thresholding analysis with an NIR band has been explored in several studies on forest areas following urban and agricultural areas [29,31,45,51]. One of the disadvantages of this technique is that it can often be difficult to distinguish shadow areas and other dark surfaces such as water bodies [45]; however, this limitation did not apply to our small study areas where no water features such as river, lake, or ocean were found.…”
Section: Shadow Removalmentioning
confidence: 98%
“…Shadow detection using a histogram thresholding analysis with an NIR band has been explored in several studies on forest areas following urban and agricultural areas [29,31,45,51]. One of the disadvantages of this technique is that it can often be difficult to distinguish shadow areas and other dark surfaces such as water bodies [45]; however, this limitation did not apply to our small study areas where no water features such as river, lake, or ocean were found.…”
Section: Shadow Removalmentioning
confidence: 98%
“…A shadow correction algorithm is relied a two-step process: detecting the location of shadow and de-shadowing. However, only a few pa-pers have described this topic in detail (Riano et al, 2003;Mather, 2004;Dare, 2005;Jensen, 2007;Ren et al, 2009;Shahtahmassebi et al, 2011). In particular, the investigations on the sequence of shadow correction (detection and de-shadowing) with respect to topographic shadow, urban shadow, cloud shadow, and composite shadow are missing.…”
Section: Introductionmentioning
confidence: 99%
“…First, although the reflectance recorded in the shadow regions is weak, there is still useful information in these areas which makes shadow restoration possible (Chen et al, 2007;Wang et al, 2008). Second, it may use surrounding information of shadowy areas (spatial information) in order to fill shadowy regions (Rossi et al, 1994;Addink and Stein, 1999;Kouchi and Yamazaki, 2007;Shahtahmassebi et al, 2011;Nole et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…cover identification results [5], [6]. Thus, the topographic normalization process is required to improve vegetation cover identification in mountainous area with high topographic variations [3], [4].…”
Section: Introductionmentioning
confidence: 99%